Neuroscience and Critique Exploring the Limits of the Neurological Turn - De Vos, Jan; Pluth, Ed (Taylor & Francis, 2016)
Recent years have seen a rapid growth in neuroscientific research, and an expansion beyond basic research to incorporate elements of the arts, humanities and social sciences. It has been suggested that the neurosciences will bring about major transformations in the understanding of ourselves, our culture and our society. In academia one finds debates within psychology, philosophy and literature about the implications of developments within the neurosciences, and the emerging fields of educational neuroscience, neuro-economics, and neuro-aesthetics also bear witness to a 'neurological turn' which is currently taking place. Neuroscience and Critique is a ground-breaking edited collection which reflects on the impact of neuroscience in contemporary social science and the humanities. It is the first book to consider possibilities for a critique of the theories, practices, and implications of contemporary neuroscience. Chapter 7 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138887336_oachapter7.pdf